Pengaruh Pendidikan, Pendapatan dan Kesadaran Terhadap Minat Masyarakat Membayar Zakat di Badan Amil Zakat Nasional (BAZNAS): Studi Kasus Kota Medan - Eri Yanti Nasution (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Zakat is an income instrument than can increase the number of Gross Domestic Product (GDP) of Indonesia. However, management system of zakat in Indonesia is still a lot of non-formal use of payment methods and that can not be realized properly. More people pay their zakah to zakah amil in mosque directly more than to the official institutions zakat in their city like BAZNAS. education, income, and awareness are three factors are considered to influencing the compliance of the people to make a formal payment of zakah. This research will analyze the most influencing factors and whether these three important factors can influence the people pay zakat in BAZNAS Medan. The population in this study is the people of Medan city consisting of 21 districts with random sampling system. The data obtained were then analyzed using descriptive analysis and regression analysis. The results showed that income positively affected the interest of the community to pay zakat in BAZNAS. This research is expected to help BAZNAS to increase public interest to pay zakat in BAZNAS and for can help Medan’s goverment to increase income